The Polish Interventional Cardiology TAVI Survey (PICTS): adoption and practice of transcatheter aortic valve implantation in Poland - Parma, Radosław; Dąbrowski, Maciej; Ochała, Andrzej; Witkowski, Adam; Dudek, Dariusz; Siudak, Zbigniew; Legutko, Jacek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction : Few studies have assessed the development of transcatheter aortic valve implantation (TAVI) in Poland since its introduction in 2008, and data on current TAVI activity or practice are missing. Aim : To assess the dynamics of TAVI adoption in Poland and to detect differences among Polish centres in TAVI practice and decision-making. Material and methods: The Polish Interventional Cardiology TAVI Survey (PICTS) was approved by the Polish Association of Cardiovascular Interventions and presented to all 21 national TAVI centres. Between 2008 and 2015 the cumulative number of TAVI performed in Poland was 2189. The annual number of TAVI rose from 8 in 2008 to 670 in 2015 (0.21 to 17.4 implants per million inhabitants, respectively). Results : The median TAVI experience per centre was 80 procedures (95% CI: 38.1–154.6). In 2015 the TAVI penetration rate reached 5.12% of the estimated eligible Polish population. Inoperable and high-risk patients are treated with TAVI in all centres, with 52% of Heart Teams also qualifying medium-risk patients. The rate of transfemoral implantations increased to 83.2% of all procedures in 2015, while transapical implantations decreased to 12%. The frequency of subclavian, direct aortic or transcarotid routes in 2015 was below 3% each. Conclusions : The PICTS survey observed a positive but slow rate of adoption of TAVI in Poland. When compared to Western European countries, our findings highlight a significant treatment gap in high or prohibitive surgical risk patients with severe aortic stenosis. Remarkable variations in TAVI practices among Polish TAVI centres warrant publication of joint national guidelines and recommendations.